Monetary policy and exchange market pressure in Malaysia - Tey, Sheik Kyin; Lee, Chin; Habibullah, Muzafar Shah (Universiti Putra Malaysia Press, 2013)
Exchange market pressure (EMP), which provides a measure of the volume of intervention necessary to achieve any desired exchange rate target, is the latest model used in the measurement of exchange rate conditions. In order to obtain a more complete picture of Malaysia’s condition and to examine how Bank Negara handles different exchange market pressures, this study considers the Malaysian exchange rate in relation to that of its two major trading partners– namely, Japan (RM/YEN exchange rate) and the United States (RM/USD exchange rate)– to construct EMP models. Monthly data from 1990:1 to 2008:9 were used in this study, and the sample period was further divided based on crisis periods and Malaysia’s experience employing different exchange rate regimes. Vector autoregression (VAR) modeling was used. The study’s findings suggest that the prescription of traditional theory was not followed by Malaysia and that Bank Negara should implement a different monetary policy with a different EMP model only under crisis and fixed exchange rate regimes.